2019
DOI: 10.34218/ijm.10.5.2019/009
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Relationship Between TQM Practices and Organizational Performance With Reference to Selected Auto Component Manufacturing Companies

Abstract: Total Quality Management (TQM) is a holistic management philosophy of continuously improving the product / service / process quality by focusing on the customer needs and expectation to enhance customer satisfaction and organizational performance. Quality management is a systematic way of guaranteeing that organized activities happen the way they are planned. TQM as long-term commitment to new learning and new philosophy is required of any management that seeks transformation. The objective is to study the TQM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The application of TQM in the organization was appear in some papers with multiple organization sector are using TQM succesfuly. Kumar & Shanmuganathan, (2019) developed a standard reliable instrument that can be used to measure the TQM implementation in an automotive component manufacturing company. The result shown that TQM has significantly influences the organizational commitment as well as the overall performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of TQM in the organization was appear in some papers with multiple organization sector are using TQM succesfuly. Kumar & Shanmuganathan, (2019) developed a standard reliable instrument that can be used to measure the TQM implementation in an automotive component manufacturing company. The result shown that TQM has significantly influences the organizational commitment as well as the overall performance.…”
Section: Resultsmentioning
confidence: 99%
“…Those 3 stages must be implemented well with the commitment from management and employees involvement and others factor such as training and communication (Kumar & Shanmuganathan, 2019).…”
Section: Introductionmentioning
confidence: 99%